New bisphosphonates in the treatment of cancer bone lesions - Charliński, Grzegorz; Wiktor Jędrzejczak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2004)
Bisphosphonates belong to compounds useful in the treatment of skeleton-related manifestations of malignancy. They are pyrophosphate analogues which are characterized by the presence of P-C-P (phosphor-coal-phosphor) structural bond. The pyrophosphates are characterized by the presence of P-O-P (phosphor-oxygen-phosphor) bond. Replacement of the coal atom by the oxygen atom prevents chemical and enzymatic hydrolysis and ensures the ability of bisphosphonate’s molecule to attach to organic matrix. When bound, it inhibits osteolysis. Based on the chemical structure, bisphosphonates are divided into those that include the nitrogen atom and those that do not. This in turn results in a different molecular mechanism of action. Nowadays, there are three generations of bisphosphonates known, which have different power of antiresorptive action on bones. About 10 new bisphosphonates have been synthesized during the last few years. They are subject to clinical trials concerning their use in clinical practice. Besides evidence on the use of bisphosphonates in the treatment of cancer bone metastases and reduction of hypercalcemia, there are also data that may suggest their usefulness in other bone diseases such as osteogenesis imperfecta, Paget’s disease and osteoporosis. This review concerns new bisphosphonates, both already registered and not registered in Poland.